MANAJEMEN PEMBELAJARAN BAHASA INGGRIS DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA SMP NEGERI 1 TAPAKTUAN ACEH SELATAN - Suwito, Cut Zahri Harun, Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: The purposeof this study is to test the ability of teachers tolearning management, e.g. planning, implementation and evaluation.The obstacles encountered by teachers are also explored. Usingdescriptive qualitative method, the research data is collectedfrom interviews, observations and documentation. The subjects of the study are English teachers and the Principal at State Junior High School No 1ofTapaktuan, South Aceh. The study finds that: (1) Planning for English lessonsconsists of building the identity of subjects, the standard of competence, basic competence, indicators, learning objectives, teaching materials, methods, allocation of time, learning activities, resources / tools,andassessment resultswhich can improve student achievement; (2) The study conducted by the teacher is still based on the syllabus of the National Education Standards Agency (BSNP). In carrying out learning activities, the English teachersare not applying innovative learning, and they are still focused on the application of conventional methods.The activities performby teachers in the implementation of learning processare:the start of classes, the delivery of  material (core activities) and the closing of the classes. In general, the process of learning in the classroom are more emphasized on the cognitive skills, meanwhile, psychomotor and affective skillsare often overlooked by the teachers;(3) the evaluation of learning were pre-test and post-test. Meanwhile, the assessment techniques used in teachingare a direct observation during the learning process and a test at the end of  each learning process. It needs to be advised that the assessment is not the goals, rather thantools;and (4) the challengescommonly faced by teachers in the planning, implementation and evaluation processaredifficult to formulate a set of indicators forachievement competency.The students frequently asked for permission to go out of class room during classes and the test items used is also difficult to analyzed. In dealing withthese obstacles, teachers are usually received guidance from senior teachers.Keywords: Management, Learning, and Student Achievement Abstrak: Tujuan penelitian ini adalah untuk mengetahui kemampuan guru dalam manajemen pembelajaran, meliputi: Perencanaan; Pelaksanaan; Evaluasi; dan Hambatan yang dihadapi guru dalam pembelajaran. Pendekatan penelitian yang digunakan adalah deskriptif kualitatif, dengan teknik pengumpulan data melalui wawancara, observasi, dan studi dokumentasi. Yang Subjek penelitian adalah guru Bahasa Inggris dan Kepala SMP Negeri 1 Tapaktuan Aceh Selatan. Hasil penelitian menunjukkan bahwa: (1) Perencanaan pembelajaran Bahasa Inggris disusun berdasarkan identitas mata pelajaran, standar kompetensi, kompetensi dasar, indikator, tujuan pembelajaran, materi ajar, metode, alokasi waktu, kegiatan pembelajaran, sumber/alat pembelajaran dan penilaian hasil belajar siswa; (2) Pelaksanaan pembelajaran yang dilakukan guru masih berpedoman pada silabus BSNP. Guru Bahasa Inggris belum menerapkan pembelajaran yang inovatif, masih terfokus pada penerapan metode konvensional. Kegiatan yang dilakukan guru dalam pelaksanaan pembelajaran yaitu membuka pelajaran, menyampaikan materi (kegiatan inti) dan menutup pelajaran. Proses pembelajaran di kelas umumnya lebih menekan pada ranah kognitif, sedangkan ranah psikomotor dan afektif sering diabaikan oleh guru; (3) Evaluasi pembelajaran adalah pre-test dan post-tes. Sedangkan teknik penilaian yang digunakan dalam pembelajaran adalah observasi langsung saat proses pembelajaran, melakukan tes/latihan diakhir pembelajaran. (4) Hambatan yang sering dihadapi guru dalam perencanaan, pelaksanaan dan evaluasi pembelajaran yaitu sulit merumuskan indikator pencapaian kompetensi, siswa sering minta permisi keluar dan sulit menganalisis butir soal tes. Dalam menghadapi hambatan tersebut, guru selalu meminta bantuan kepada guru senior.Kata kunci: Manajemen, Pembelajaran, dan Prestasi Belajar Siswa